Risk factors for osteoporosis in Japan: is it associated with Helicobacter pylori? - Asaoka D; Nagahara A; Shimada Y; Matsumoto K; Ueyama H; Matsumoto K; Nakagawa Y; Takeda T; Tanaka I; Sasaki H; Osada T; Hojo M; et al. (Dove Medical Press, 2015)
Daisuke Asaoka, Akihito Nagahara, Yuji Shimada, Kenshi Matsumoto, Hiroya Ueyama, Kohei Matsumoto, Yuta Nakagawa, Tsutomu Takeda, Ippei Tanaka, Hitoshi Sasaki, Taro Osada, Mariko Hojo, Sumio Watanabe Department of Gastroenterology, University of Juntendo, School of Medicine, Tokyo, Japan Background: A number of diseases and drugs may influence bone mineral density; however, there are few reports concerning the relationship between lifestyle-related diseases and osteoporosis in Japan as determined by multivariate analysis. The aim of this study was to investigate the risk factors for osteoporosis and whether infection by or eradication of Helicobacter pylori is associated with osteoporosis.Methods: Between February 2008 and November 2014, using a cross-sectional study design, we investigated patient profile (age, sex, BMI, alcohol, smoking), H. pylori infection status, comorbidities, internal medicine therapeutic agents (calcium channel blocker, HMG-CoA reductase inhibitors, proton pump inhibitor), serum parameters (Hb, calcium, ΥGTP), bone turn over markers (bone-specific alkaline phosphatase (BAP) and collagen type I cross-linked N telopeptide (NTX), findings on dual-energy x-ray absorptiometry (DEXA) and upper gastrointestinal endoscopy, and Frequency Scale for the Symptoms of GERD score in consecutive outpatients aged ≥50 years at our hospital. We divided the subjects into an osteoporosis group and a non-osteoporosis group and investigated risk factors for osteoporosis between the two groups by bivariate and multivariate analyses.Results: Of the 255 eligible study subjects, 43 (16.9%) had osteoporosis. Bivariate analysis showed that advanced age, female sex, lower body mass index, lower cumulative alcohol intake, lower Brinkman index, H. pylori positivity, lower hemoglobin, bone-specific alkaline phosphatase, lower prevalence of hiatal hernia, and endoscopic gastric mucosal atrophy were related to osteoporosis. Multivariate analysis showed that advanced age (odds ratio [OR] 1.13, 95% confidence interval [CI] 1.07–1.19, P<0.001), female sex (OR 6.27, 95% CI 2.26–17.39, P<0.001), low BMI (OR 0.82, 95% CI 0.72–0.94, P=0.005), H. pylori positivity (OR 3.00, 95% CI 1.31–6.88, P=0.009), and BAP (OR 1.07, 95% CI 1.01–1.14, P=0.035) were related to osteoporosis.Conclusion: Advanced age, low BMI, BAP, and H. pylori positivity were risk factors for osteoporosis; however, the success of H. pylori eradication was not a risk factor for osteoporosis in Japan. Keywords: osteoporosis, risk factor, Helicobacter pylori, eradication, proton pump inhibitor, lifestyle disease